Identità narrativa e melanconia - Galabru, Sophie (B@belonline, 2021)
Our aim is to see how melancholia is a remarkable disorder of narrative identity: the patient can still tell her or his life story, or even write it, but she or he cannot construct a narrative in the ricœurian sense, nor can she or he understand herself or himself according to a dynamic identity. With the help of Freudian literature and three selected melancholic narratives, we will be able to put the Ricœurian theory of narrative identity into a problematic perspective.